Urban demographic growth : the case of megacities - Sobrino, Jaime (CEDUA-COLMEX, 2021)
One of the main facts about contemporary urbanization consists on the accelerated increase in the number of megacities. Megacities have been defined by the United Nations (UN) as urban concentrations containing more than 10 million people (United Nations, 2010). In 1950 there were only two metropolis with that reaching that number (New York and Tokyo), while in 1980 two more were added (Mexico City and Säo Paolo), and for 2010 there were 21, where 324 million people were living, 4.7% of the world population. The objective of this chapter is to analyze the evolution of megacities from a demographic perspective, their role on the urban national systems where they are located, and their economic and competitiveness importance in the global sphere.